Properties of zeros of solutions to third order nonlinear differential equations - Smirnov, Sergey (Mathematical Modelling and Analysis, 2013)
We investigate the behavior of zeros of solutions to the certain type of third order nonlinear differential equations. We show that the behavior of zeros may be rather different and depend on the nature of nonlinearity in the equation. Main results in the paper are illustrated with a number of examples.